Sempre o bem dos pobres: o pastor Oscar Romero, o teólogo Jon Sobrino e o povo salvadoreño (um tríptico eclesial e sua atualidade para o século XXI) - Silva, Rogério Mosimann da (2012)
The intention of this study is to relate the bishop Oscar Romero (his public performance, his practice and his pastoral heart, elements which are reflected in the words of his homilies) with the theologian Jon Sobrino. Representatives of complementary ecclesial charisms, both can only be understood against the background of Salvadoreño believer and poor people, particularly the people of the Christian Base Communities (Comunidades Eclesiais de Base, or CEBs), third element of a triptych. Sobrino is representative of the Latin American theology of liberation and a privileged interpreter of Romero. Deep coincidences occur between both (substantive and epistemological issues) that enlighten each other. From Sobrino's writings, we collect both direct allusions to Romero as the implicit presence of this pervading the thinking of the theologian. By valuing the historical dimension and memory, our research does not propose the task of the historian. And reflecting on theological themes, does not constitute a systematic study. Attention is directed to the discussion of how significant experience of the recent and so dense past can follow illuminating our present and our future. We found ourselves, as a threshold, so that this work can be inserted into the line of a fundamental theology for Latin America in the XXI century, since it put the question for some of the conditions for theological thinking in our continent in the next decades. Constant concern is the issue of timeliness of Romero. Apart from the enormous differences, we identify important similarities between our framework and his own, particularly regarding the reality of the poor. The practice of Romero reveals itself as a historical concretion of what is permanent in the Gospel. Encountering God in the encounter with the poor expresses the core of his Christian experience (spiritual and pastoral). This is enshrined in the expression always the good for the poor, a metaparadigm that exceeds the contingencies of every age and need to be constantly reaffirmed. This assumption that the option for the poor is something that remains synthesizes a facet also in the nuclear theology of Jon Sobrino. In this interlacing of retrospective and prospective, we seek to collect an inheritance, and ask for its pertinency to new historical circumstances. Questions thus emerge: what does it mean for the poor the great transformations of today, the vaunted change of epoch? How to continue assuming the reality of unjust poverty, and the cry and life itself of the impoverished people, crucified (albeit with new faces), as larger fact, central mediation and structural axis of a theology that purports to follow the walk of victims? How to develop a consistent reflection that takes account of the new situation in the world, but to do so in dialogue with the liberating tradition and the heritage of irruption of the poor? We recognize thereby the relevance of the liberating dimension for today, without locating it in a supposedly already surpassed past (which would amount to a replacement scheme "before the liberation, and now the new paradigms"). Our study also allowed a glimpse of a subtle struggle for image and identity of Romero, by the interpretation of his legacy. Our belief is that being historically committed to the cause of the poor is the best reading key to enter into the spirit of Romero. Moving away from this perspective, the interpreter distances himself from Romero himself. Finally, from the experience of Romero is highlighted the dimension of the proximity to the poor. Since then we postulate the possibility of a marginal theology that, without renouncing reflexive rigor, seeks to more closely follow the daily life of those who inhabit the peripheries of our world.